Diet overlap of three sympatric species of Leptodactylus Fitzinger (Anura: Leptodactylidae) in a Protected area in the Brazilian Amazon - Baia, Raimundo R. J. (2020)
Closely related species are often similar in morphological and ecological characters, which may lead them to compete when occurring in sympatry. In this sense, we analyzed trophic niche overlap among three Leptodactylus species, Leptodactylus macrosternum, L. fuscus and L. aff. podicipinus, in a floodplain environment from a Protected area in the Brazilian Amazon. In addition, we applied Network and Non-metric multidimensional scaling (NMDS) analysis. We found 18 prey categories, most of them belonging to Arthropoda (94.4%). Coleoptera, Isoptera, Diptera and Hymenoptera were the most abundant prey on the diet shared among the three species. The rarefaction curve of prey richness did not reach an asymptote, indicating that the diet composition may be higher by increase the sample. The species presented a broad niche breadth, however, no relationship between jaw width and prey size were found in the studied species. Despite the line-up in NMDS with Bray Curtis Index indicated that the species’ diets are similar with few different attributes, with some food items overlapping among species (Stress= 0.00201), the niche overlap between the pair of species was not high (Ojk < 0.7). Therefore, we believe interactions such as competition would be better demonstrated addressing data on prey availability and microhabitat use patterns.